ANALISIS PENGARUH TINGKAT PENDAPATAN, TINGKAT PENDIDIKAN, SUKU BUNGA, PENETRASI DEMOGRAFIS DAN GEOGRAFIS PERBANKAN TERHADAP TOTAL KREDIT UMKM (Studi kasus Kota dan Kabupaten di Jawa Tengah Tahun 2011-2015) - Rahman, Mizan Ikhlasul; Widyarti, Endang Tri (Diponegoro Journal of Management, 2017)
Financial inclusion becomes international interest and national priority. The more inclusive financial access, the more opportunity people have to improve their economy. Financial inclusion has become an alternative way to grow economy of society. Credit is one of financial services which can improve people’s economy, specifically for SME in capital credit. This research examines effects from factors such as people income, education level, interest rate, demographic and geographic penetration of banking to SME credit. Samples selected in this research by total sampling method. Samples used are 35 cities and regencies at Central Java in 2011-2015. Data analysis using data panel regression analysis with Fixed Effect Model and Generalized Least Square. This research shows that people income has insignificant positive effect to SME credit, education level has significant negative effect, intereset rate has insignificant negative effect, demographic penetration of banking has insignificant positive effect and geographic penetration of banking has significant positive effect.